Inovasi Alih Media Arsip Tanah (ADIARTA) Oleh Dinas Perpustakaan dan Kearsipan Kota Batu - Eka Wahyu Ningtyas (Universitas Negeri Surabaya, 2026)
Land records are an important asset for villages and urban villages in supporting the continuity of governmental activities. However, the organization and maintenance of land archives in villages/urban villages in Batu City have not been well managed, and cases of abuse of authority by officials remain prevalent. These conditions encouraged the Batu City Office of Library and Archives to carry out archive digitization through the Website-Based Land Archive Media Conversion Innovation (ADIARTA), which involves the digital management of Letter c and krawangan land records to ensure the long-term availability of land information. This study aims to analyze the implementation of the ADIARTA innovation by the Batu City Office of Library and Archives using a descriptive qualitative method, with data collected through interviews, observations, and documentation. The analysis is based on the e-government innovation model proposed by Choi and Chandler (2020), which includes the background of e-government emergence, the introduction of e-government innovation, and implementation factors. The results indicate that the ADIARTA innovation has generally been implemented well as a response to land archive management issues that previously relied on manual systems and has contributed to improving the security and sustainability of land archives. However, its implementation has not yet been fully optimal due to limitations in human resources and scanning equipment, insufficient outreach and socialization, and the absence of binding regulations, which allows villages and urban villages to retain the authority to refuse the implementation of the ADIARTA innovation.